How Costly is Financial (Not Economic) Distress? Evidence from Highly Leveraged Transactions that Became Distressed - Andrade, Gregor; Kaplan, Steven N. (Journal of Finance, 1998)
This paper studies thirty-one highly leveraged transactions (HLTs) that become financially, not economically, distressed. The net effect of the HLT and financial distress (from pretransaction to distress resolution, market- or industry-adjusted) is to increase value slightly. This finding strongly suggests that, overall, the HLTs of the late 1980s created value. We present quantitative and qualitative estimates of the (direct and indirect) costs of financial distress and their determinants. We estimate financial distress costs to be 10 to 20 percent of firm value. For a subset of firms that do not experience an adverse economic shock, financial distress costs are negligible.